A novel hexagonal wideband circularly polarized stacked patch microstrip antenna. Issue 11 (November 2015) - Mondal, Tapas; Samanta, Susamay; Ghatak, Rowdra; Chaudhuri, Sekhar Ranjan Bhadra
ABSTRACT This article proposes a novel, simple, microstrip‐fed, circularly polarized, stacked, diagonal‐slotted, wideband hexagonal microstrip patch antenna for Intelligent Transport System (ITS) applications. It has been found to operate in the Global Positioning Systems frequency L1 (GPS 1.575 GHz). The fabricated antenna shows an impedance bandwidth of 171 MHz which is around 11% (1.521–1.692 GHz) with 3 dB axial‐ratio‐bandwidth (ARBW) of 80 MHz which is around 5% (1.54–1.62 GHz) and for the entire 3 dB ARBW the gain achieved is over 6.5 dBi. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2548–2554, 2015